2016
DOI: 10.1186/s13046-016-0436-6
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA H19 regulates FOXM1 expression by competitively binding endogenous miR-342-3p in gallbladder cancer

Abstract: BackgroundLong non-coding RNA (lncRNA) H19 has been reported to involve in many kinds of human cancers and functions as an oncogene. Our previous study found that H19 was over-expressed in gallbladder cancer (GBC) and was shown to promote tumor development in GBC. However, the competing endogenous RNA (ceRNA) regulatory network involving H19 in GBC progression has not been fully elucidated. We aim to detect the role of H19 as a ceRNA in GBC.Methods and ResultsIn this study, the expression of H19 and miR-342-3p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 57 publications
4
83
0
2
Order By: Relevance
“…On the contrary, Yu et al reported that H19 potentiated choriocarcinoma cell apoptosis [12]. In our study H19 inhibited apoptosis and promoted the proliferation of gastric cancer cells, which is consistent with other recent studies [23-25]. It has been established that miR-675 derives from the firs exon of H19, and miR-675 has been reported as being at least partially responsible for the regulation of H19 function [26, 27].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…On the contrary, Yu et al reported that H19 potentiated choriocarcinoma cell apoptosis [12]. In our study H19 inhibited apoptosis and promoted the proliferation of gastric cancer cells, which is consistent with other recent studies [23-25]. It has been established that miR-675 derives from the firs exon of H19, and miR-675 has been reported as being at least partially responsible for the regulation of H19 function [26, 27].…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, our data demonstrate that H19/miR-675 could target FADD, increase pro-caspase 8/3, and inhibit apoptosis. In addition to H19/miR-675 axis, H19 also can regulate tumorigenesis through other mechanisms involving other H19 exons besides the first one [37, 38]. Therefore the analysis of the function of H19 with mutation in the exon 1 is needed in the future to illuminate possible new mechanisms and ruling out the effect of miR-675.…”
Section: Discussionmentioning
confidence: 99%
“…None of these associations, however, have been reported in the literature. On the other hand, studies have demonstrated hits on the gene regulation between hsa-miR-142-5p and CD24 [86], hsa-miR-29 and DNMT3B [87, 88], hsa-miR-142-3p and EGR2 [89], hsa-miR-150 and EGR2 [90], hsa-miR-34a and IKZF3 [91], hsa-miR-150 and MIAT [92], hsa-miR-342-3p and PSMG3 [93, 94], hsa-miR-17 and TIMP3 [95]. Our results further suggested an important correlation between miRNAS and gene expression values in both Basal I and Basal II, identified by this in silico approach.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of lncRNAs have been identified as playing critical roles in cancer development and progression [43-45]. LncRNA H19 is located on the 11p15.5 locus and functions as an oncogene in several cancers [46-48]. Here, we initially analyzed lncRNA microarray profiles to identify candidate lncRNAs associated with the cytotoxic role of Huaier extract.…”
Section: Discussionmentioning
confidence: 99%